Effect of feeding wastelage on intake and digestibility of nutrients in adult buffaloes - YADAV, SUNIL; KHRWAR, S S; YADAV, K R (The Indian Journal of Animal Sciences, 2013)
Four wastelages incorporating, 70 (T2),60 (T3) and 50% (T4) cattle waste with wheat straw as roughage and 80 parts wheat straw and 20 parts deoiied rice bran as control (T1) were prepared. Urea in graded levels was added to raise the protein content (12-13%) al 40% moisture level. These silages were fed to 4 adult fistulated buffaloes in 4 X 4 latin-square design for 24 days in each switch over. The dry-matter intake decreased significant (P